ANALYSIS OF THE EFFECTIVENESS OF BUS SERVICES OUTSIDE OF CAMPUS IPB DRAMAGA BOGOR - Syaiful, Syaiful; Fadly, Ahmad (ASTONJADRO, 2020)
IPB Dramaga Bogor's Off-Campus Bus is one of the transportation programs to support IPB's civitas activities. IPB's Off-Campus Bus Program is also one of the supporting programs of IPB's green campus in 2020 Based on IPB Rector's Decree Number 205 / IT3 / LK / 2015 concerning the implementation of the green movement campus 2020 in the IPB environment, one of which is green transportation. Purpose To get a calculation of the effectiveness of bus services outside the Dramaga IPB route Jl.Raya Sukasari, Jl.Raya KH Sholeh Iskandar and Jalan Pancasan ciapus in the year Conducting an analysis of the effectiveness of off-campus bus services in Dramaga IPB using the Likert scale method. The limitation of this research problem includes security , safety, comfort, affordability, equality and order. The method used in this study is the linkert scale. Based on the results of the discussion with the Likert scale method the results obtained in the form of a presentation score answer variable bus transportation services outside the campus Dramaga IPB of 67.87% and included in the class interval 60% -79.99% which means it is included in the Good category.